PEMEROLEHAN BAHASA PADA ANAK USIA 2 TAHUN DILIHAT DARI ASPEK FONOLOGI - Ulman, Sonia; Priyanto, Agus; Mustika, Ika (IKIP Siliwangi, 2021)
This article discusses language acquisition in children aged 2 years in terms of phonology. The purpose of this study was to analyze and describe language acquisition regarding aspects of vowel or consonant phonology in children aged 2 years. The research subject is a 2 year old child named RSH. This study used descriptive qualitative method. This technique uses data resulting from observations by inviting the child's direct communication, then the data is processed through appropriate exposure to the data in the field. The results obtained from this study show that the acquisition of RSH phonology, especially in vowels, has been mastered, but there are several vowels that are sometimes replaced, for example vowel [o] becomes [u], but so far, RSH has mastered the vowels [a], [i] , [u], [e], [o]. The first vowels he mastered were the vowels [a] and [u]. Likewise, the consonant sounds [b], [t], [h], [w], [y], [n], [m], [p], [j] have been well mastered. If the consonant sound is in the middle, the utterance has been obtained even though it is not correct, but if you find a consonant sound at the end of a word, RSH always interchanges it with a consonant sound [h].